2004
DOI: 10.1159/000078202
|View full text |Cite
|
Sign up to set email alerts
|

Positional changes of pericentromeric heterochromatin and nucleoli in postmitotic Purkinje cells during murine cerebellum development

Abstract: Previous studies revealed changes of pericentromeric heterochromatin arrangements in postmitotic Purkinje cells (PCs) during postnatal development in the mouse cerebellum (Manuelidis, 1985; Martou and De Boni, 2000). Here, we performed vibratome sections of mouse cerebellum (vermis) at P0 (day of birth), at various stages of the postnatal development (P2–P21), as well as in very young (P28) and 17-months-old adults. FISH was carried out on these sections with major mouse satellite DNA in combination with immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
47
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(55 citation statements)
references
References 15 publications
8
47
0
Order By: Relevance
“…Although it has been previously shown that the localization, number, and size of major satellite regions change during neural development (Billia et al, 1992;Solovei et al, 2004Solovei et al, , 2009, we now show the first evidence that these changes are accompanied by a change in the chromatin state and transcriptional activity of this region. The major satellite regions are traditionally considered to be "silent" regions located within the heterochromatin and marked by repressive histone modifications.…”
Section: Discussionsupporting
confidence: 40%
See 2 more Smart Citations
“…Although it has been previously shown that the localization, number, and size of major satellite regions change during neural development (Billia et al, 1992;Solovei et al, 2004Solovei et al, , 2009, we now show the first evidence that these changes are accompanied by a change in the chromatin state and transcriptional activity of this region. The major satellite regions are traditionally considered to be "silent" regions located within the heterochromatin and marked by repressive histone modifications.…”
Section: Discussionsupporting
confidence: 40%
“…Histone H3 lysine-4 trimethylation becomes localized to chromocenters during neuronal differentiation Because of the previous observation that the number, location and size of major satellite foci change during neuronal development, we asked whether neuronal differentiation is also accompanied by changes in the chromatin state of these regions (Billia et al, 1992;Solovei et al, 2004Solovei et al, , 2009). We used immunostaining to examine histone modifications, a reflection of chromatin state, in major satellite regions during neuronal differentiation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…genomic loci. Indeed, the composition of the nuclear lamina, the position and architectural changes of the nucleolus, and the sequestration of genomic loci and regulatory proteins into promyelocytic leukemia (PML) bodies, nuclear speckles, histone locus bodies, transcription factories, Cajal bodies, and others have all been linked to gene regulation across a variety of cell types (Solovei et al 2004;Peric-Hupkes et al 2010;Sleeman and Trinkle-Mulcahy 2014).…”
mentioning
confidence: 99%
“…Live-cell observations of movements of a GFP-tagged transgene array in a mammalian cell line (CHO) yielded long-range movements over distances of 1-5 m at velocities from 0.1 to 0.9 m/min (34). Large-scale movements were also observed in nuclei during postmitotic cell differentiation, but these movements required a time scale of days rather than hours (35). In conclusion, it seems unlikely that directed chromatin movements of an extent required for kissing events between widely separated loci take place during interphase.…”
Section: Discussionmentioning
confidence: 84%